Strategi Potensi Pengurangan Emisi Karbon dari Aktivitas Perkebunan dan Pabrik Kelapa Sawit - Muhammad Abil Khausa; Suwondo Suwondo; Eni Sumiarsih (Pelantar Press, 2026)
The potential for carbon emission reductions from palm oil plantation and mill activities at PT Perkebunan Nusantara IV Region III represents a critical contribution to Indonesia's national commitment to achieving Net Zero Emissions by 2060. Operational activities—including fuel combustion in heavy machinery, generator utilization, fertilization, electricity consumption, and liquid waste treatment through Palm Oil Mill Effluent (POME) contribute significantly to greenhouse gas (GHG) emissions, particularly carbon dioxide (CO₂), methane (CH₄), and nitrous oxide (N₂O). This study employs a quantitative approach grounded in SNI ISO 14064-1:2018, systematically calculating emissions under Scope 1, Scope 2, and partial Scope 3 categories across three operational units: Lubuk Dalam, Terantam, and Sei Pagar. The findings reveal that mobile combustion constitutes the largest emission source, followed by stationary combustion, fertilization activities, and fugitive emissions derived from POME processing. Among the three units examined, the Terantam unit generates the highest total emissions. Further analysis demonstrates that the utilization of biogas (CH₄) recovered from POME holds substantial energy generation potential, capable of producing 950,174 kWh at Lubuk Dalam, 1,929,734 kWh at Terantam, and 880,749 kWh at Sei Pagar, with an aggregate economic value exceeding Rp 4 billion annually. Based on these findings, three principal mitigation strategies were formulated: substituting diesel-powered generators with grid electricity supplied by PLN, transitioning heavy equipment to electric-based technology, and optimizing biogas utilization for electricity generation. These strategies demonstrate significant potential not only in reducing CO₂ equivalent (CO₂e) emissions but also in enhancing energy efficiency and advancing the long-term operational sustainability of the company